The beauty in imperfection: how naturalness cues drive consumer preferences for ugly produce and reduce food waste - Xiao, Meizhen; Jiang, Yi; Cao, Binbin (Frontiers in Sustainable Food Systems, 2023)
Purpose An important reason for food waste is the rejection of ugly produce by consumers. Most previous research has examined the absolute negative impacts of ugly produce on consumers’ preferences, no research has examined the conditions in which consumers prefer ugly (vs. typical) produce instead.This research investigates the circumstances under which these aesthetic imperfections become advantageous. Methods We conducted two between-subject design randomized experiments featuring two produce categories to examine when and why consumers prefer ugly produce. Results We found that naturalness cues boost and even reverse consumers’ preferences for ugly produce when combining ugly appearance with naturalness cues. The subtyping effect mediates the interaction of appearance (typical vs. ugly) of produce and naturalness cues (present vs. absent) on produce’s evaluations. Discussion Our findings provide more cost-effective strategies for retailers to reduce food waste. This paper fills in the research gaps on taping into the novel condition in which consumers prefer ugly (vs. typical) produce and the psychological mechanism behind this process. Based on schema incongruity theory, we argue that naturalness cues, as an enabler corresponding to the incongruous features of ugly produce, facilitate consumers to resolve the schema incongruity triggered by the ugly appearance and, in turn, boost consumers’ preferences for ugly produce.